Forgotten Little Words: How Backchannels and Particles May Facilitate Speech Planning in Conversation? - Knudsen, Birgit; Creemers, Ava; Meyer, Antje S. (Frontiers in Psychology, 2020)
In everyday conversation, turns often follow each other immediately or overlap in time. It has been proposed that speakers achieve this tight temporal coordination between their turns by engaging in linguistic dual-tasking, i.e., by beginning to plan their utterance during the preceding turn. This raises the question of how speakers manage to co-ordinate speech planning and listening with each other. Experimental work addressing this issue has mostly concerned the capacity demands and interference arising when speakers retrieve some content words while listening to others. However, many contributions to conversations are not content words, but backchannels, such as ‘hm’. Backchannels do not provide much conceptual content and are therefore easy to plan and respond to. To estimate how much they might facilitate speech planning in conversation, we determined their frequency in a Dutch and a German corpus of conversational speech. We found that 19% of the contributions in the Dutch corpus, and 16% of contributions in the German corpus were backchannels. In addition, many turns began with fillers or particles, most often translation equivalents of ‘yes’ or ‘no’, which are likewise easy to plan. We proposed that to generate comprehensive models of using language in conversation psycholinguists should study not only the generation and processing of content words, as is commonly done, but also consider backchannels, fillers, and particles.